2021
DOI: 10.1097/dss.0000000000003275
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Device-Based Cutaneous Channels Using Optical Coherence Tomography: Impact for Topical Drug Delivery

Abstract: BACKGROUND Topical medications play a large role in the management of cutaneous diseases, but penetration is limited. Device-assisted drug delivery using mechanical destruction, lasers, and other energy-based modalities can increase penetration and absorption through creation of transcutaneous channels. OBJECTIVE To examine real-time, in vivo cutaneous changes in response to various devices used to improve topical drug delivery through optical coherence tomography (OCT) imaging. METHODS AND MATERIALS Treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…The use of this oil formulation allowed the API to be delivered to the skin at a higher concentration (222. 19 ] are effective when used alone in facilitating the penetration of ibuprofen. The main constituents of these oils included ligustilide (79.32%), ligustilide (41.00%), (E)-cinnamaldehyde (83.30%), and eugenol (80.22%), respectively.…”
Section: Natural Compounds With the Penetration-enhancing Potential O...mentioning
confidence: 99%
See 1 more Smart Citation
“…The use of this oil formulation allowed the API to be delivered to the skin at a higher concentration (222. 19 ] are effective when used alone in facilitating the penetration of ibuprofen. The main constituents of these oils included ligustilide (79.32%), ligustilide (41.00%), (E)-cinnamaldehyde (83.30%), and eugenol (80.22%), respectively.…”
Section: Natural Compounds With the Penetration-enhancing Potential O...mentioning
confidence: 99%
“…Moreover, active and passive methods are used to facilitate TDD. Active methods involve the use of external energy to increase the penetration of active pharmaceutical ingredients (APIs) through the skin by using electrical energy (iontophoresis, electroporation), ultrasound (sonophoresis), radiofrequency electromagnetic waves (radiofrequency), and laser energy. These methods include mechanical techniques such as micropuncture to create pores in the SC for APIs. Passive methods involve the interactions between the drug, vehicle, and SC layer. They aim to modify the API physicochemical properties, e.g., by changing its solubility or ionization and/or leading to an increase in skin permeability.…”
Section: Introductionmentioning
confidence: 99%
“…Microneedles can be of various bores and lengths, with or without insulation or radiofrequency energy, and hence, may behave differently. Although a recent study using optical coherence tomography found that microneedling and radiofrequency microneedling did not create observable cutaneous channels, other recent research suggests that in some cases microneedling may facilitate increased penetration and greater lateral extension of the drug as compared with AF laser …”
Section: Resultsmentioning
confidence: 96%
“…7 Their patterns of thermal injury are different. 13 Greater contact duration and protrusion distance with this particular device can create larger effects. This has benefits for fibroblast proliferation and collagen production, and unlike fractional CO2 laser, the craters associated with fractional thermomechanical injury are clean of necrotic tissue or charring.…”
Section: Discussionmentioning
confidence: 98%